2021
DOI: 10.14689/ejer.2021.94
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Purpose: Scientific literacy plays an important role in catalyzing science learning in the 21 st century. Unfortunately, previous evidence revealed that students' scientific literacy tends to be unsatisfactory. This study investigated the effect of ethnosciencethemed picture books embedded in context-based learning (EthCBL) on students' scientific literacy. Methods: In this quasi-experimental research, 58 (35 girls and 23 boys) fifth-grade students in a public elementary school in Indonesia were selected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Although the studies on UbD in Turkey are not as much as the studies conducted in the international arena, there has been an increase in the number of these studies in our country in recent years. These studies focus on UbD-based unit design training as part of teachers' professional development (Yurtseven, 2016;Yurtseven & Altun, 2018;Yurtseven & Doğan, 2018) or the impact of UbD-oriented instructional design within a discipline on students (Durmaz, 2014;Geylan, 2021;Oflaz, 2019;Özyurt, Kan & Kıyıkçı, 2021;Uluçınar, 2018;Uluçınar & Dinç, 2021;Yurtseven, 2016;Yurtseven & Doğan, 2018;Yurtseven, Doğan & Altun, 2013;). Although it is stated that the results of these studies contribute to the professional competencies of teachers and significant developments in the characteristics of students such as success and attitude, it is observed that in most studies on UbD in Turkey, the basic steps and principles of UbD are not followed sufficiently or explanations about these processes are not made.…”
Section: Reviewing Studies On Ubd In Turkeymentioning
confidence: 99%
“…Although the studies on UbD in Turkey are not as much as the studies conducted in the international arena, there has been an increase in the number of these studies in our country in recent years. These studies focus on UbD-based unit design training as part of teachers' professional development (Yurtseven, 2016;Yurtseven & Altun, 2018;Yurtseven & Doğan, 2018) or the impact of UbD-oriented instructional design within a discipline on students (Durmaz, 2014;Geylan, 2021;Oflaz, 2019;Özyurt, Kan & Kıyıkçı, 2021;Uluçınar, 2018;Uluçınar & Dinç, 2021;Yurtseven, 2016;Yurtseven & Doğan, 2018;Yurtseven, Doğan & Altun, 2013;). Although it is stated that the results of these studies contribute to the professional competencies of teachers and significant developments in the characteristics of students such as success and attitude, it is observed that in most studies on UbD in Turkey, the basic steps and principles of UbD are not followed sufficiently or explanations about these processes are not made.…”
Section: Reviewing Studies On Ubd In Turkeymentioning
confidence: 99%